Pengaruh Debt Default Terhadap Opini Audit Going Concern Dengan Komite Audit Sebagai Variabel Moderasi - Tsalatsa Rahma Salsabila; Imang Dapit Pamungkas (Faculty of Economics and Business, University of Pancasakti Tegal, 2025)
This study aims to analyze the effect of debt default on going concern audit opinions, moderated by the audit committee. The population used in this research comprises basic materials companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample was selected using a purposive sampling method, resulting in 40 companies and 117 research observations. The analytical methods using WarpPLS version 7.0. The findings indicate that debt default has a significant positive effect on going concern audit opinions. However, the audit committee is unable to moderate the relationship between debt default and going concern audit opinions.